Relationship of Obesity and Peak Expiratory Flow Rate (PEFR) amongst 8-15 Years Old School Children (Bangladesh Journal of Child Health, 2017)
Background: Obesity is rapidly escalating worldwide in all age groups. Childhood obesity is associated with a greater long-term risk of hypertension and type 2 diabetes mellitus in adulthood.Objectives: To observe the relationship of peak expiratory flow rate (PEFR) with obesity.Methods: Two hundred students were selected from two different schools of Narayanganj city by following inclusion criteria- for group A: BMI of > 95th percentile for age and sex was taken as obese and for group B: BMI of 10th- 85th percentile for age and sex was taken as non-obese. The anthropometric measurements and PEFR were measured by standard procedure.Results: PEFR were found statistically significant in non-obese than obese groups (p